1999
DOI: 10.1021/la9815190
|View full text |Cite
|
Sign up to set email alerts
|

On the Adsorption of Formaldehyde at High Temperatures and Zero Surface Coverage

Abstract: The adsorption of formaldehyde (HCHO) at very low vapor concentration (zero surface coverage) is studied on several carbon materials by using inverse gas−solid chromatography (IGC). The adsorption process is carried out in the Henry's law region. Therefore, the specific retention volumes, V s, allow the determination of the standard enthalpy of adsorption, ΔH o A, using the linear relationship between ln V s vs 1/T. Nevertheless two linear plots are obtained for the adsorption of HCHO on these carbon materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…On the porous materials they are expected to be twice greater reaching about 30 kJ/mol for ethane and 70 kJ/mol for acetone (32). On the other hand, the heat of formaldehyde adsorption on various activated carbons was found to be between 15 and 33 kJ/mol (10). Following this, and Avgul and Kiselev's evaluation of the heat of one CH 3 moiety on nonporous carbon black equal to 9 kJ/mol (30), the heat of acetaldehyde obtained on microporous carbons should be in the range of 33-51 kJ/mol.…”
Section: Fig 4 Dtg Curves In Nitrogenmentioning
confidence: 96%
See 1 more Smart Citation
“…On the porous materials they are expected to be twice greater reaching about 30 kJ/mol for ethane and 70 kJ/mol for acetone (32). On the other hand, the heat of formaldehyde adsorption on various activated carbons was found to be between 15 and 33 kJ/mol (10). Following this, and Avgul and Kiselev's evaluation of the heat of one CH 3 moiety on nonporous carbon black equal to 9 kJ/mol (30), the heat of acetaldehyde obtained on microporous carbons should be in the range of 33-51 kJ/mol.…”
Section: Fig 4 Dtg Curves In Nitrogenmentioning
confidence: 96%
“…It also must be able to retain the sorbed odoriferous compound at even close to saturation conditions. Adsorption of formaldehyde on activated carbons was studied by Domingo-Garcia et al (10). They found that formaldehyde is strongly adsorbed with isosteric heat between 15 and 33 kJ/mol.…”
Section: Introductionmentioning
confidence: 99%
“…2 In this sense, the maximum concentration of HCHO in residential dwellings and workplaces has been strictly regulated. Many technologies have been used to address the removal of HCHO from air, both in laboratories and in fields,3 including plant absorption,4, 5 plasma technology,6 physical adsorption,7, 8 photocatalysis,9–11 and catalytic oxidation 12. 13 Among these technologies, physical adsorption has advantages in terms of its low cost and easy operation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the adsorption capacity depends mainly on the textural characteristics, i.e., porous structure and pore volume, the surface nature can condition in many cases (1, 2) the adsorption behavior in solution, in the gas phase, and also the activity as catalyst and catalyst support (3,4). This means that the adsorption behavior of the activated carbons cannot be easily explained only on the basis of textural characteristics (surface area and pore size distribution); the chemical surface nature must also be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…pends on the treatment to which they are submitted. For instance, acidic groups are produced when activated carbons are treated in solution with different oxidizing agents such as HNO 3 , KClO 3 , and H 2 O 2 , or in the gas phase with O 2 , CO 2 , or steam. However, these treatments, in most cases, produce a modification of the textural characteristics of the original activated carbon, which can be a drawback in carbon materials with a narrow microporosity or a well-defined porosity.…”
Section: Introductionmentioning
confidence: 99%